Early cognitive predictors of spelling and reading in German-speaking children - Sigmund, Jan Luis; Mehlhase, Heike; Schulte-Körne, Gerd; Moll, Kristina (Frontiers in Education, 2024)
While reading and spelling skills often are interconnected in models of literacy development, recent research suggests that the two skills can dissociate and that reading and spelling are associated with at least partly different cognitive predictors. However, previous research on dissociations between reading and spelling skills focused on children who have already mastered the first phases of literacy development. These findings suggest that dissociations are due to distinct deficits in orthographic processing (i.e., unprecise orthographic representations vs. inefficient serial processing). It is therefore unclear whether dissociations already become apparent during the initial stages, or rather emerge later in development. This study aims to enhance the understanding of the predictors of early spelling and reading skills, investigating potential variations, by considering various cognitive factors beyond well-established ones.Data were collected at two time points: cognitive predictors and early reading and spelling skills were assessed at the end of kindergarten (T1) before formal literacy instruction started, and reading and spelling skills were again assessed in Grade 1 (T2). The data analysis included 353 first-grade participants. Linear regression analyses assessed predictive patterns, while logistic regression analyses explained children's likelihood of belonging to different proficiency groups (at-risk or typical skills).Results revealed phonological processing, letter knowledge, and intelligence, as significant predictors for Spelling in grade 1 (T2), even after adding the autoregressor (Spelling in kindergarten at T1) and the respective other literacy skill (Reading T2). For Reading in grade 1 (T2), phonological processing, and rapid automatized naming (RAN) surfaced as significant predictors after adding the autoregressor (Reading T1). However, only RAN surfaced as a significant predictor for Reading T2 after adding the respective other literacy skill (Spelling T2). In line with these findings, logistic regression analyses revealed that phonological processing predicted group allocation for Spelling T2 and RAN predicted group allocation for Reading T2.Overall, the study underscores the importance of phonological processing and letter knowledge as early predictors of spelling and reading skills in Grade 1. Moreover, intelligence is identified as a predictor for early spelling, while rapid automatized naming (RAN) emerges as a predictor for early reading.